Assessment methods in pastures with or without animals - RAMOS, BARBARA; Teles Cruz, Natan; José Vieira Pires, Aureliano; Maia de Lana Sousa, Braulio; Rodrigues Jardim, Renata; Deitos Fries, Daniela; Lucas Santos Dias, Daniel; Bonomo, Paulo; Louise Pacheco Ramos, Bárbara (Pubvet, 2021)
The objective of this review was to address the evaluation methods carried out in plant experiments with or without animals. In general, pasture areas in Brazil are the main sources of food for ruminants, since the country has a large territorial area composed of several forage plants. In this sense, understanding how forage canopies behave during a given management strategy is of fundamental importance for the development of pasture management. Therefore, it is necessary to make use of evaluation methods that allow the estimation of a desired variable, serving as a basis for the definition of decision-making. The evaluation techniques in pastures are divided into direct and indirect, where each method has its peculiarity resulting in variable estimates when compared to each other. Furthermore, in addition to the choice of method used, experimentation in pastures should integrate the plant’s response to climatic variation, and if possible, the presence of the animal in the system. In this way, it is possible to simulate the pasture ecosystem within the experimentation and be extrapolated to agricultural production systems. Thus, the efficiency of these systems can be improved through forage planning developed on a scientific basis.